Implementasi Metode Preference Selection Index Dalam Penentuan Penerimaan Beasiswa Pada SMA Negeri 2 Bengkulu Selatan - Andika Kurniawan; Yovi Apridiansyah; Yulia Darmi; Harry Witriyono (JUKOMIKA (Jurnal Ilmu Komputer dan Informatika), 2023)
Scholarships are a form of assistance given to students or students in the form of funds or money that will be used to help the cost of the educational process and ease the burden on students in taking the study period, especially the cost issue, given a selective scholarship program.Â  This study aims to implement the Preference Selection Index (PSI) method in determining scholarship acceptance at SMA Negeri 2 South Bengkulu. This study uses a quantitative approach by using secondary data in the form of a decision matrix containing criteria for determining scholarship acceptance and data on students who have applied for scholarships in the previous year. The PSI method is used to determine the relative weight of each criterion and calculate the final score for each student. The results of this study show that the PSI method can produce objective and fair decisions in determining scholarship acceptance. In the application of the PSI method, the criterion with the highest weight is academic achievement and the criterion with the lowest weight is activeness in student organizations. The results of this study can be used as recommendations for the school in determining scholarship acceptance in the following years. It is hoped that the results of this study can help schools in selecting students who meet the criteria and deserve scholarship assistance to help with their education costs.